A Comprehensive Review of Mathematical Modeling Approaches for Analysing Human Reproductive Dynamics in North East India - Lumina Devi, Laishram (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
North East India, characterized by its ethnic diversity and varied socio-economic conditions, encounters distinct reproductive health challenges driven by early marriage, cultural norms, and disparities in healthcare access. Early marriage contributes to early childbearing and affects fertility rates. Diverse cultural practices among the region's numerous ethnic groups shape family planning decisions and contraceptive use, while limited access to quality healthcare services exacerbates maternal and child health issues. This review paper examines how mathematical modeling can provide a structured approach to understanding these complex dynamics. The application of age-structured and fertility transition models is analysed to track demographic trends and shifts in fertility. Additionally, advanced modeling techniques, such as stochastic and agent-based models, are used to account for variability and simulate different scenarios. The review also evaluates data collection methods for accurate modeling and the processes of calibration and validation. The findings underscore the effectiveness of these models in capturing regional reproductive trends and highlight the need for improved data collection and the integration of local cultural and socio-economic factors into models to enhance their accuracy and relevance. By combining quantitative models with qualitative insights, this review aims to offer actionable recommendations for developing public health strategies and policies tailored to the specific needs of North East India.​